Preservation of marine biodiversity for health and wellbeing of the society in the age of technological advances: Islamic and marine science perspective - Mohammad Noor, Normawaty; Hashi, Abdurezak Abdulahi (Universiti Putra Malaysia, 2021)
The ocean covers more than 70% of the earth, while the life and health of various living things depend on the oceans. Healthy marine life is therefore important for sustainable and healthy environment for all living things, especially hu- man beings, not only in the sense of having a sustainable ecosystem but also in having healthy marine resources for consumption. With advances in mass production technology, the oceans are hit by the mass waste dumbing, which has poisoned and intoxicated the health of marine life and its biodiversity in many ways. The high marine biodiversi- ty of the ocean provides us with various kind of food with different taste, high in protein, vitamin, minerals and chem- ical compounds for medicinal purposes. Besides the challenges of dumbing industrial waste, the modern advances in technology and usage of sophisticated machines, ships, and other unfriendly human activities have deteriorated the quality of the ocean and caused the marine biodiversity and its health resources to decrease. The importance of marine biodiversity has been mentioned many times in the Qur’an, covering many aspects such as the benefits and usage of the ocean, the conditions and laws of the ocean, the status of marine resources in terms of consumption and the needs to protect the marine life. Therefore, in the paper, researchers will use systematic review and comparative analysis to discuss the impact of technological advances in the marine life health and its implication on community health. While addressing actors causing the decrease of marine biodiversity, the paper aims to explore solutions to such problems from Islamic and marine sciences perspectives.